IMPLEMENTASI PROGRAM MADRASAH ADIWIYATA DALAM UPAYA MENUMBUHKAN SIKAP PEDULI LINGKUNGAN DI MI RADEN BAGUS TALOK - Ahdiana Ela Nihayatul Khusna; Fita Mustafida; Zuhkhriyan Zakaria (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2022)
This Adiwiyata program is a program designed since 2004 by the Ministry of Education and Environmental Culture which has the aim of creating a good environment for school residents, both students, teachers and staff in schools through educative, participatory and sustainable principles. This research was conducted at MI Raden Bagus Talok which is one of the schools implementing the Adiwiyata program. The method used is descriptive qualitative which uses data in the form of written or spoken words from observable people and actors. The technique used in collecting data is by interview, observation and document retrieval. The findings of this study indicate that the implementation of the Adiwiyata program at MI Raden Bagus has been going well, starting from the provision of infrastructure and activities that support the implementation of the Adiwiyata program. The principal fully supports the Adiwiyata program by making policies and also the parents of students who are involved in the implementation of the Adiwiyata program. However, there are also obstacles, namely the lack of complete tools and materials and also the surrounding community who are less concerned about environmental cleanliness. And the efforts made by schools for the implementation of the Adiwiyata program are by increasing the example of teachers as role models, giving punishments and rewards as well as participatory-based activities. Keywords: Adiwiyata Program, Care for the environment